ANALISIS DESKRIPTIF LEVEL PERTANYAAN PADA SOAL CERITA DI BUKU TEKS MATEMATIKA SMK PROGRAM KEAHLIAN RUMPUN SENI, PARIWISATA, DAN TEKNOLOGI KERUMAHTANGGAAN KELAS XI PENERBIT PUSAT PERBUKUAN DEPARTEMEN PENDIDIKAN NASIONAL BERDASARKAN TAKSONOMI SOLO - Septriana, Maharani Dewi; Hobri, Hobri; Fatahillah, Arif (Department of Mathematics Education , University of Jember, 2016)
The goal of this research aims to describe the percentage of each level question about the narrative question on mathematics textbook for second class of SMK for art, tourism, and household technology skill program based on SOLO taxonomy. The data used in the research is form of narrative questions on the mathematics textbook. To analyze the data, we use descriptive approach. The result of this research was precentage of level question based Taxonomy SOLO. Therefore, the percentage of Unistructural Level are 0%; Multistruktural Level are 49,52%; Relasional level are 50,48%; and Extended Abstrack Level are 0%.